Tunable Multiwavelength Passively Mode-Locked Fiber Ring Laser Using Intracavity Birefringence-Induced Comb Filter - Zhi-Chao Luo; Ai-Ping Luo; Wen-Cheng Xu; Hai-Sen Yin; Jia-Rui Liu; Qing Ye; Zu-Jie Fang (IEEE Photonics Journal, 2010)
A simple configuration for the generation of tunable multiwavelength picosecond-pulse fiber ring lasers by exploiting the intracavity birefringence-induced comb filter is demonstrated. The fiber laser is passively mode locked by using nonlinear polarization rotation (NPR) technique. The polarization-dependent isolator combined with the intracavity birefringence acts as two functions: the tunable comb filter and the mode locker. Up to four-wavelength picosecond pulses were simultaneously obtained in the experiment. The mode competition of the multiwavelength lasing is suppressed by the use of NPR-induced intensity-dependent loss. In addition, the number of the lasing wavelengths, the lasing location, and the spacing between the lasing wavelengths could be flexibly tuned by properly rotating the polarization controllers.